Cohort profile: biomarkers related to folate-dependent one-carbon metabolism in colorectal cancer recurrence and survival - the FOCUS Consortium - Gigić, Biljana; Roekel, Eline van; Holowatyj, Andreana N.; Brezina, Stefanie; Geijsen, Anne J. M. R.; Ulvik, Arve; Ose, Jennifer; Koole, Annalenn; Damerell, Victoria; Kiblawi, Rama; Gumpenberger, Tanja; Lin, Tengda; et al. (BMJ open, 2022)
Purpose The overarching goal of the FOCUS (biomarkers related to folate-dependent one-carbon metabolism in colorectal cancer (CRC) recurrence and survival) Consortium is to unravel the effect of folate and folate-mediated one-carbon metabolism (FOCM) biomarkers on CRC prognosis to provide clinically relevant advice on folate intake to cancer patients and define future tertiary prevention strategies. - Participants The FOCUS Consortium is an international, prospective cohort of 2401 women and men above 18 years of age who were diagnosed with a primary invasive non-metastatic (stages I-III) CRC. The consortium comprises patients from Austria, two sites from the Netherlands, Germany and two sites from the USA. Patients are recruited after CRC diagnosis and followed at 6 and 12 months after enrolment. At each time point, sociodemographic data, data on health behaviour and clinical data are collected, blood samples are drawn. - Findings to date An increased risk of cancer recurrences was observed among patients with higher compared with lower circulating folic acid concentrations. Furthermore, specific folate species within the FOCM pathway were associated with both inflammation and angiogenesis pathways among patients with CRC. In addition, higher vitamin B6 status was associated with better quality of life at 6 months post-treatment. - Future plans Better insights into the research on associations between folate and FOCM biomarkers and clinical outcomes in patients with CRC will facilitate the development of guidelines regarding folate intake in order to provide clinically relevant advice to patients with cancer, health professionals involved in patient care, and ultimately further tertiary prevention strategies in the future. The FOCUS Consortium offers an excellent infrastructure for short-term and long-term research projects and for combining additional biomarkers and data resulting from the individual cohorts within the next years, for example, microbiome data, omics and multiomics data or CT-quantified body composition data.
Gesehen am 10.05.2023